Psychological distress among patients receiving haemodialysis in a teaching hospital - Maharjan, Jyoti (Journal of Patan Academy of Health Sciences, 2022)
Introduction: A psychological distress is highly prevalent conditions among haemodialysis patients, but is often under diagnosed and untreated. It could have negative impacts on their treatment and prognosis of the disease. The purpose of this study was to assess the prevalence of psychological distress in the patients receiving haemodialysis in a teaching hospital. Methods: This quantitative cross-sectional study comprised of 59 patients of Chronic Kidney Disease (CKD) receiving haemodialysis at Patan Hospital. The respondents were selected using purposive sampling technique. After taking informed consent, data was collected using interview technique based on structured questionnaires. Depression Anxiety Stress Scale-21 was used to assess the levels of depression, anxiety and stress. Data was analyzed using descriptive statistics in terms of mean, frequency and percentage. Results: The prevalence of depression, anxiety and stress were 71.18%, 62.71% and 20.33% respectively. Majority (30.51%) of the respondents had moderate depression, 20.34% had mild, 10.17% had severe and extremely severe depression. Similarly, 32.20% had moderate anxiety, 15.25% had mild, 6.78% had severe and 8.47% had extremely severe anxiety. Likewise, 11.86% had mild stress, 6.78% had moderate stress, and 1.69% had severe stress. The mean and standard deviation of DASS scores were 34.51 ± 19.31. The prevalence of psychological distress among respondents was 42.37%. Conclusions: The results of the study showed that more than two fifth of the respondents had psychological distress. The highest prevalence was depression which was present in more than two third of the respondents.